2018
DOI: 10.1126/sciadv.aaq1438
|View full text |Cite
|
Sign up to set email alerts
|

Differential expression of voltage-gated sodium channels in afferent neurons renders selective neural block by ionic direct current

Abstract: Researchers investigate the use of ionic direct current to reverse the standard neural stimulation recruitment order.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
34
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(40 citation statements)
references
References 36 publications
5
34
1
Order By: Relevance
“…The authors' explanation for how this block could occur is that during cathodic DC application, the voltage gated sodium channels are held in their inactivated states, preventing AP propagation (Bhadra and Kilgore, 2004). This argument is further supported by the investigation of the peripheral afferent cathodic block (Yang et al, 2018).…”
Section: Electrical Stimulation—neuron Interactionmentioning
confidence: 76%
See 3 more Smart Citations
“…The authors' explanation for how this block could occur is that during cathodic DC application, the voltage gated sodium channels are held in their inactivated states, preventing AP propagation (Bhadra and Kilgore, 2004). This argument is further supported by the investigation of the peripheral afferent cathodic block (Yang et al, 2018).…”
Section: Electrical Stimulation—neuron Interactionmentioning
confidence: 76%
“…In support of prediction 5, ionic channel conductances during DC presentation appear to critically influence the neural response (Yang et al, 2018). This was indicated with a neural block experiment in which a cathodic block exhibited different thresholds on different neuronal fiber types, which could not be explained entirely via differences in fiber diameter.…”
Section: Electrical Stimulation—neuron Interactionmentioning
confidence: 85%
See 2 more Smart Citations
“…Experimental data indicated that the Na v 1.1 and Na v 1.6 channels are preferentially expressed in the nodes of mammalian peripheral nerve fibers [49][50][51]. We substituted the HHtype models of I Naf and I Nap in node 6 to node 14 with the Markov-type models of Na v 1.1 and Na v 1.6 channels, respectively.…”
Section: Implementation Of Markov-type Vgscsmentioning
confidence: 99%